Uncertainty and design practice in China. The “apparatus” of Shanghai experimental architecture - Santi, Ettore (Journal of Architecture and Urbanism, 2017)
Professional architects and scholars in China have pointed out the issue of uncertainty in the everyday realm of the design practice. Experimental architecture firms, the Chinese-born ateliers committed to seeking the “Chinese Identity” of architecture, have accepted uncertainty as a constitutive category of the process of city making and claimed they are learning from it. Yet, the cultural and political genealogy of uncertainty in China’s design process has not been significantly investigated. Building on the Foucauldian notion of apparatus, this paper unpacks the condition of uncertainty in Shanghai’s experimental architecture design practice and examines the formal and informal negotiations of power emerging among the diverse actors taking part in this process. Those include conflicts between governments at different levels, the contingency of the market demands, overlapping roles of design consultants, dynamics of cultural capital within the academic institutions. Based on methods of participant observation of experimental architecture ateliers in Shanghai, this analysis conveys that the Chinese Identity of architecture, the center of experimental architect’s design research, emerges as a consequence of the dynamics of the apparatus rather than from an a-priori formal determinism.